The use of virtual reality-assisted interventions on psychological well-being and treatment adherence among kidney transplant recipients: A randomized controlled study - Chao Zhong; Lin Yao; Lanlan Chen; Xiaofen Wang; Xiaohui Zhu; Yihong Wen; Lei Deng; Jiafu Chen; Jialiang Hui; Lisha Shi; Lijuan You (Acta Psychologica)
This randomized controlled trial aims to investigate the effects of educational and psychological interventions on the health outcomes of patients suffering from chronic diseases. We recruited 372 patients and randomly assigned them to one of two intervention arms during the trial, which lasted for a year. Both groups participated in a 12-month intervention program, where the intervention group received health education and supportive psychological therapy utilizing virtual reality (VR) technology, while the control group received conventional health education guidance. Statistical analysis showed that compared to the control group, the intervention group demonstrated significant improvements (p < 0.05) in depression assessment scores, compliance scores, and Barthel functional scoring. However, the two groups had no significant difference in the incidence of complications and health knowledge mastery. Additionally, the intervention group had fewer hospitalization days than the control group, with statistically significant differences. The research results prove that targeted intervention effectively improves medication adherence, patient awareness, and reduces patient hospitalization days, which is particularly important for managing chronic diseases.